Mustang Roundup, July 1945 (1945)
The campus newspaper and yearbook ceased publication for the duration of the war, and were replaced in October 1942 with the Mustang Roundup. The news-humor magazine appeared monthly, edited jointly by civilian and naval students under the direction of Robert Kennedy.